Interventional neuroradiology - Hetts, Steven W.; Cooke, Daniel L. (Handbook of clinical neurology, 2021)
"Interventional Neuroradiology, Volume 179, provides a basic outline of the field of interventional neuroradiology that is accessible to fellows, residents, clinicians and researchers in various disciplines, from diagnostic and interventional radiology to vascular neurology, general and vascular neurosurgery, and vascular biology. This volume offers a timely update to experienced clinical practitioners in a logical, easy-to-follow format. Content includes neurovascular anatomy, vascular biology, neurovascular physiology, vascular imaging, as well as sections on the diagnosis and therapeutic treatment of neurovascular disease"--Publisher's description